IIUM's experience in teaching creative thinking skills - Badi, Jamal Ahmed Bashier (2014)
This keynote speech was delivered in Arabic. It highlights the historical background of developing the subject, its syllabus, content, challenges in offering and teaching it and approaches used to overcome them.